A thermally insulated solar evaporator coupled with a passive condenser for freshwater collection. Issue 39 (27th September 2021) - Cheng, Shuwen; Sun, Zhehao; Wu, Yang; Gao, Peng; He, Jiaxin; Yin, Zongyou; Liu, Liying; Li, Gang
Abstract : A solar evaporation and passive electricity-independent freshwater recovery unisystem to achieve high evaporation efficiency and freshwater recovery rate through an evaporator consisting of carbonized reed stalk arrays and a chimney-like condenser. Abstract : Using solar energy to generate vapor and using passive freshwater collectors are sustainable and eco-friendly approaches to address the issue of clean water scarcity. The current challenge for solar evaporation is to develop facile manufacturing materials and scalable methods with high solar conversion efficiency by heat localization. In addition, a decrease in the solar evaporation rate due to humidity saturation in the evaporation chamber is also a reason for the lower freshwater collection rate. In this paper, we demonstrate a solar-driven, interfacial evaporation-based and passive electricity-independent desalination unisystem, which consists of an evaporation chamber that uses hydrophilic and low-cost carbonized biomass full of water transportation microchannels, for the first time, as a solar evaporator. Meanwhile, the designed external aluminum condenser of the condensation chamber realizes freshwater collection. With improved designs and repeated tests, such a desalination unisystem achieves a stable evaporation rate of 1.492 kg m −2 h −1 and solar-to-vapor conversion efficiency of ∼90.8% under 1 sun. It also simultaneously generates freshwater with a collection efficiency of ∼85.4% compared to the evaluated water evaporation rate in the open atmosphere. This portable, easily implemented, and nonenergy-consuming desalination unisystem has the potential to provide new inspiration for the realm of seawater desalination and wastewater treatment.